Enhancing Marine Tourism Management as a Blue Economy Strategy to Boost Community Welfare in Jayapura City, Papua Province - Nasim, Eman Sulaiman (Majalah Ilmiah Bijak, 2025)
This research aims to explore marine tourism management as a blue economy strategy in improving community welfare in Jayapura City, Papua Province. The research used qualitative methods with observation, in-depth interviews, and documentation. The results show that the potential for marine tourism in Jayapura includes 19 beach locations, such as Base G Beach and Hamadi Beach, which can become leading destinations. However, major challenges are faced, including legal uncertainty regarding land ownership, lack of public transportation infrastructure, and low quality of human resources in the tourism sector. Social factors such as the liquor culture and unsupportive behavior of local communities are also obstacles. The Jayapura City Government's efforts through human resource training, facility development, and promotion have not been successful in fully increasing tourist arrivals or the tourism sector's contribution to Regional Original Revenue (PAD). The contribution of this sector is still less than 3% to PAD. This study recommends the application of the Pentahelix collaboration model, which involves government, industry, academia, community and media, to optimize marine tourism management. In addition, the development of community-based homestays through collaboration with platforms such as Traveloka and AirBnB can increase destination attractiveness. With a more inclusive and sustainable strategy, marine tourism in Jayapura City has great potential to improve community welfare and drive local economic growth.